Analysis of the Implementation of Ijarah Muntahiya Bittamlik Contracts in Indonesian Sharia Banking Institutions - Nathania Felisiana Lukita Devy (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the implementation of the Ijarah Muntahiya Bittamlik (IMBT) contract in Indonesian Sharia banking and to assess its compliance with Sharia principles and the fatwas (religious rulings) of the National Sharia Board of the Indonesian Council of Ulama (DSN-MUI). A normative-juridical research method with a qualitative approach was employed, utilizing a literature review of primary, secondary, and tertiary legal sources. The findings indicate that the implementation of IMBT in Sharia banking has evolved and is utilized across various financing products, such as those for vehicles, property, and other productive assets. However, there are variations in practice among banks, particularly regarding contract structures, ownership transfer mechanisms, and risk management. Regarding Sharia compliance, the implementation of IMBT generally adheres to DSN-MUI fatwas; nevertheless, potential deviations persist, such as the suboptimal separation of contracts and issues concerning asset ownership. Therefore, strengthening regulations, enhancing Sharia supervision, and standardizing implementation are necessary to ensure that IMBT contracts operate in substantive accordance with Sharia principles.